PENGARUH LATIHAN FISIK MAKSIMAL AKUT TERHADAP KADAR ESTRADIOL TIKUS PUTIH BETINA (Rattus norvegicus strain wistar) - Rahmawati Rahmawati (Universitas Batanghari Jambi, 2014)
Nowadays women have become increasingly active in competitive physical activities and more women are entering the world of sport to become profesional athletes. For those reasons, they may do or maximal strenuous exercise. However, the maximal physical exercise can adversely impact the menstrual cycle due to increase in oxygen free radicals. Short maximal physical exercise, nevertheless, is able to reduce oxygen fre radicals and incrase anti-oxidant. This study is aimed at determining the effect of acute maximal physical exercise on estradiol level in female whit rats (Rattus norvegicus strain wistar).This study is an experimental research design using post test only control group design of 32 female whit rats divided into 2 groups: the control group and the treatment group. Each group consisting of 16 rats respectively were given physical trainig 2 times a day for 30 minutes in the form of swimming for 5 days. Once treatment is completes and the data obtained, the data is processed using the statistical t-test.The research findings show that the average estradiol level of female white rats in the treatment group was 4.39 nmol/L with a standard deviation 0,36 nmol/L, whereas the average estradiol lever for female white rats in the control group was 2,63 nmol/L with a standard deviation 0,19 nmol/L. The statistical tet result show p-value = 0.0001, which means that, at th 5% alpha, there appears significant differences in the average estradiol levl between female white rats in the control group and the treatment group about 7.6 times as high.From these findings, it can bbe concluded that the short maximal physical exercise can increase estradiol level in female white rats. Therefore further research is required to look at the effct of acute maximal physical exercise on the female athlete’s estradiol level.Keyword: estrogen, maximal physical xercise, acute phhysical exercise